Mastering NServiceBus and persistence : design and build various enterprise solutions using NServiceBus while utilizing persistence enterprise objects /: design and build various enterprise solutions using NServiceBus while utilizing persistence enterprise objects. (2014) - Helton, Rich
No abstract available